On properties of the graph of fuzzy topographic topological mapping - Sayed, Mohamed (2013)
Fuzzy Topographic Topological Mapping (FTTM) is a novel noninvasive technique to determine the location of epileptic foci in epilepsy disorder patients. The model which consists of topological and fuzzy structure is composed into three mathematical algorithms. There are two FTTMs, namely FTTM Version 1 and FTTM Version 2. FTTM Version 1 is homeomorphic to FTTM Version 2. The homeomorphism of FTTM can be presented using graphs. This paper presents some properties of the graph of FTTM.